(untitled) (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
This study aims to analyze the risk of energy loss in ship fabrication processes at PT DUMAS Shipyard Surabaya using a Bayesian Network modeling approach. Energy losses were identified across six key processes: Sandblasting, Painting, Cutting, Forming, Welding, and Lifting Equipment (cranes, hoists, and forklifts). The Bayesian method was employed to model the probabilistic relationships among causal variables, including air pressure, cooling system performance, machine idle time, equipment condition, and operator behavior, all of which contribute to potential energy loss. Risk assessment was conducted by calculating likelihood and consequence values based on the AS/NZS 4360:2004 standard to determine the level of energy-related risk in each process. The results indicate that the Welding process has the highest probability of energy loss at 0.25 and is classified as a High Risk. Cutting, Sandblasting, and Painting fall under the Moderate Risk category, while Forming and Lifting Equipment are categorized as Low Risk. Recommended mitigation strategies include implementing automatic control systems for key equipment, enhancing operator training, and optimizing pneumatic and cooling systems. The energy risk evaluation serves as a basis for improving efficiency within the fabrication processes.